Comments to the Article “The Gods as Latent Causes: A Statistical Inference Theory of Religion”, by Francesco Rigoli & Jack Lennon - Oviedo Torró, Lluís (The international journal for the psychology of religion, 2025)
This paper engages with the target article and the proposed theory of religious beliefs as a means to address the variance between expectations and reality. Three main issues emerge that need to be addressed in order to make this theory more reasonable. The first concerns the complexities of belief and probability estimation, as this approach needs to be better placed within current developments in epistemology and psychology. The second addresses the cultural evolution of religious beliefs and the challenge of relating them to a theory of dual cognitive styles: intuitive and reflective. The third issue highlights the need to expand the theory to include an existential framework, emphasizing the need for meaning-making.